GAMBARAN SISTEM PENGAJUAN KLAIM PASIEN RAWAT INAP BPJS KESEHATAN DI RSUD X KABUPATEN BANDUNG: DESCRIPTION OF THE CLAIM SUBMITTING SYSTEM OF BPJS INPATIENT AT HOSPITAL X IN BANDUNG REGENCY - Winarti, Wiwin; Sukmawati, Tania Defi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2022)
The BPJS Health program has been launched for more than six years, but the process of making claims from the hospital to the BPJS Health Office continues to be developed. In line with the policy changes issued by the BPJS Health regulations, hospitals must also follow these changes, for the smooth payment of claims, so that the cash flow of hospital operations is not disrupted. This paper aims to find out the system for submitting claims for BPJS Health inpatients at RSUD X, Bandung Regency. The location of data collection is in the BPJS Health Inpatient Claim Unit, RSUD X Bandung Regency, on June 14-24, 2021. The type of paper uses descriptive qualitative research, using data collection techniques of observation, interviews, and documentation. Observations were made at the BPJS Health Inpatient Claim Unit at RSUD X Bandung Regency, then interviews were conducted with two BPJS Health inpatient claims officers, as well as documentation of the claim requirements file. The collected data is then analyzed to conclude. The result of writing is that the claim file and the submission of BPJS Health inpatient claims at RSUD X Bandung Regency are in accordance with the references used,